MAKNA LANSIA DALAM QS. YĀSĪN [36]: 68 : Telaah Ma‘nā Cum-Maghzā Terhadap Realitas Kehidupan Usia Senja di Modern - Mukhlis; Amelia Yetri (STAI AL-ANWAR SARANG, 2024)
This study analyzes QS. Yāsīn [36]: 68 in the context of elderly life using the Ma‘nā Cum-Maghzā approach, which integrates historical meaning analysis, historical phenomenal significance, and dynamic phenomenal significance. This research aims to explore the verse’s meaning in a more contextual and relevant manner, addressing the social, psychological, and spiritual challenges faced by the elderly in the modern era. The research method used is library research, reviewing primary sources such as classical and contemporary tafsir books, as well as hermeneutic literature related to the concept of aging in Islam. The findings show that QS. Yāsīn [36]: 68 not only describes the biological process of aging but also conveys profound theological and sociological messages. From a historical meaning perspective, the verse emphasizes the concept of naks (weakening), which represents the human life cycle from strength to weakness. In terms of historical phenomenal significance, the verse highlights human limitations and the importance of spiritual preparedness in facing old age. Meanwhile, from the perspective of dynamic phenomenal significance, this verse has relevance in addressing the challenges of the elderly, such as social isolation, identity crises, and the need for spiritual guidance. The implications of this research include strengthening the role of religion in providing spiritual support for the elderly, enhancing elderly participation in meaningful social activities, and developing policies based on Islamic values to improve the well-being of the elderly.